Trends of rhinoplasty research in the last decade with bibliometric analysis - Zhu, Xuanru; Zhang, Bin; Huang, Yuesheng (Frontiers in Surgery, 2023)
Background As rhinoplasty (RP) with different requirements is becoming more and more popular in the latest decade, this study aims to quantitatively and qualitatively explore the trends in RP research, depict research hotspots, and point out the future direction with a bibliometric analysis. Methods All RP literature studies in the last decade (from 2012 to 2021) were retrieved from the Web of Science Core database. Annual output, institutions, authors, journals, and most-cited literature studies were analyzed by bibliometric tools, including CiteSpace, bibliometric online platform, bibliometrix R language kit, BICOMB, and gCLUTO. Results A total of 2,590 RP research studies dated between 2012 and 2021 were included according to our criterion. As for the country, the United States, Turkey, and Korea maintained the top three in RP research. As for the institutions, the University of California, Irvine, Stanford University, and University of Ulsan ranked top three in RP research publications based on article counts. Professor Rhorich RJ, Most SP, and Jang YJ were the most contributed authors according to article counts and citation number. The top journals were The Plastic and Reconstructive Surgery, JAMA Facial Plastic Surgery, and Aesthetic Surgery Journal. The 10 most-cited literature studies were also listed explicitly in this study. Finally, biclustering analysis on the most frequent keywords were conducted which helped us to identify seven hotspot clusters in RP research. Conclusions We comprehensively summarized the publication information of RP literature studies in the past decade, highlighted the current status and trends over time, and provide guidance for in-depth research direction on RP for the future.